The Complexity of Relationships between Individuals, Society, and Power in the Literary Works of Al-Mutanabbi - Nurhilaliah Fitri Sholehah; Astri Khodimatus Sholihah; Channah Qotrunnada; Rizzaldy Satria Wiwaha; Dadan Rusmana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Al-Mutanabbi ranks as one of the most renowned poets in the history of Arabic literature, with his poems reflecting his complex personality and ambitions. This research aims to explore the main themes in Al-Mutanabbi's works, such as identity, self-pride, praise, social critique, and commentary on societal dynamics. By employing textual analysis and historical study methods, this research examines how Al-Mutanabbi used poetry to express his thoughts, construct his self-image, and deliver critiques of social conditions and patronage relationships during his time. The findings reveal that Al-Mutanabbi consistently projected a strong sense of confidence and pride in his works, portraying himself as a great poet. He built relationships with rulers through laudatory poems but also expressed bold criticism of opponents and the societal conditions of his era. His immense ambition is evident in his works, which often highlight the conflict between personal aspirations and the socio-political challenges of the Abbasid era. This study provides new insights into the relationship between a poet's life and the literary works he produces. It also emphasizes how poetry serves as a tool for constructing self-identity and responding to the dynamics of power in the classical era.